3D printed gelatin/decellularized bone composite scaffolds for bone tissue engineering: Fabrication, characterization and cytocompatibility study. (June 2022) - Kara, Aylin; Distler, Thomas; Polley, Christian; Schneidereit, Dominik; Seitz, Hermann; Friedrich, Oliver; Tihminlioglu, Funda; Boccaccini, Aldo R.
Abstract: Three-dimensional (3D) printing technology enables the design of personalized scaffolds with tunable pore size and composition. Combining decellularization and 3D printing techniques provides the opportunity to fabricate scaffolds with high potential to mimic native tissue. The aim of this study is to produce novel decellularized bone extracellular matrix (dbECM)-reinforced composite-scaffold that can be used as a biomaterial for bone tissue engineering. Decellularized bone particles (dbPTs, ∼100 ​μm diameter) were obtained from rabbit femur and used as a reinforcement agent by mixing with gelatin (GEL) in different concentrations. 3D scaffolds were fabricated by using an extrusion-based bioprinter and crosslinking with microbial transglutaminase (mTG) enzyme, followed by freeze-drying to obtain porous structures. Fabricated 3D scaffolds were characterized morphologically, mechanically, and chemically. Furthermore, MC3T3-E1 mouse pre-osteoblast cells were seeded on the dbPTs reinforced GEL scaffolds (GEL/dbPTs) and cultured for 21 days to assess cytocompatibility and cell attachment. We demonstrate the 3D-printability of dbPTs-reinforced GEL hydrogels and the achievement of homogenous distribution of the dbPTs in the whole scaffold structure, as well as bioactivity and cytocompatibility of GEL/dbPTs scaffolds. It was shown that Young's modulus and degradation rate of scaffolds were enhanced with increasing dbPTs content. Multiphoton microscopy imaging displayed the interaction of cells with dbPTs, indicating attachment and proliferation of cells around the particles as well as into the GEL-particle hydrogels. Our results demonstrate that GEL/dbPTs hydrogel formulations have potential for bone tissue engineering. Graphical abstract: Image 1